Radiation diagnostics of vision organ’s traumatic damages - Ikramov, A. I.; Karieva, Z. S. (Ukrainian Neurosurgical Journal, 2010)
On the basis of 96 patients investigation results with orbit integrity infringement from 245 injured persons with craniofacial trauma, been hospitalized to clinics of the Republic Scientific Centre of emergency medical aid and Republic Scientific Centre of neurosurgery of Republic Uzbekistan in the period from 2003 to 2009 years the possibilities of radiation methods (CT, MRT, ultrasonic, ultrasonic with Doppler scanning) in emergency diagnostics of orbit traumatic injury with various damages of vision organ’s structures were studied and early complications of eyeball contusion were revealed in order for timely prevention of visual functions loss.